EFFECT OF EDUCATION FUND, THE NUMBER OF INFRASTRUCTURE, HR EFFECTIVENESS OF TEACHER EDUCATION PROGRAM - Selfiani Selfiani (EAJ (Economic and Accounting Journal), 2019)
This study aims to determine the effect of education funds, the amount of infrastructure, human resources of teachers to the effectiveness of education programs. The population in this study is sepill provincial education in Indonesia in 2016. The sample amounted to 34 provinces with the observation of 34 local revenue balance. The observation is conducted for one year, in 2016. The Data used are secondary Data, among others derived from the income balance of the province in Indonesia, especially the vocational school is determined through purposive sampling. Data analysis was done by hypothesis tested by linear regression method. The results of this study indicate that funds educational, teaching personnel affect the effectiveness of educational programs, while the amount of infrastructure does not affect the effectiveness of educational programs.